ENHANCING STUDENTS’ VOCABULARY MASTERY BY APPLYING DICTOGLOSS TECHNIQUE TO THE ELEVENTH GRADE STUDENTS OF SMA DELI MURNI BANDAR BARU IN THE ACADEMIC YEAR OF 2020/2021 - Pinem, Nancy Srimina Br; Pangaribuan, Jontra Jusat; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2021)
This research was primarily conducted to prove that the application of Dictogloss technique could enhance the vocabulary mastery of the eleventh grade students of SMA Deli Murni Bandar Baru Bonaventura Class in the Academic Year of 2020/2021 and to describe their responses towards the application of Dictogloss technique in the process of learning vocabulary mastery. This research is Classroom Action Research which was perfomed in two cycles. Each cycle consisted of four meetings. The quantitative data analysis showed that the students mean score increased continually from 44,16 in pre-test, 59,17 in formative test, and 70,83 in post-test. And the percentage of the students who passed the mastery minimum criteria from pre-test to post-test is 60,39%. The qualitative data analysis showed that the students responses after being taught by using Dictogloss technique. It can be seen from observation sheets and field notes; they felt more enthusiastic and motivated to learn vocabulary mastery after Dictogloss technique was applied. The questionnaire data also showed that students are agree with the application of using Dictogloss technique and found it effective in teaching vocabulary mastery. It is suggested that English teachers using Dictogloss technique as an alternative media in teaching vocabulary to the students in Senior High School in order to enhance their students’ vocabulary mastery.